An Analysis of Madurese Language Interference in the English Pronunciation of EFL Students at SMP Negeri 1 Randuagung - Muhammad Rikwan; Widya Oktarini; Kristi Nuraini (FKIP - Universitas Riau, 2026)
This study aims to analyze and describe the forms of Madurese language interference on the pronunciation skills of EFL students at SMP Negeri 1 Randuagung. The study uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The results show that Madurese language interference appears predominantly in the phonological aspect, especially in the form of consonant substitution (/v/ to /f/, /ʃ/ to /s/, and /θ/ to /t/), difficulty in distinguishing long and short vowels, omission of final consonants, rigid and monotonous intonation. This pattern of errors indicates phonological transfer from the mother tongue, which affects students' English pronunciation. These findings support the theory of language transfer, which states that the sound system of the first language influences the production of sounds in the second language. Pedagogically, these research results emphasize the importance of phonetic awareness-based pronunciation learning strategies and sound contrast exercises to reduce the influence of the mother tongue and improve students' pronunciation accuracy.